(3GdcTa hGdHjGf aj JaSjQ GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdCYQGa s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI GdfMd cGedI s
(3HBNQgG eWGdYg ef GSeGYjd GdOQYi SfI (B820s
(3GdhQbI GdChdi HNW eZGjQ MOjKs
(3fSNI cJHJ HNW Cgd GdfbW ajg CMjGfkG s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs